MANAJEMEN LABA DAN REPUTASI AUDITOR - Yossi Diantimala (Program Magister Akuntansi Unsyiah, 2010)
This paper is aimed to examine the difference of earnings management between firms audited by Big Four Auditor and firms audited by non-Big Four Auditor. Sample is randomly selected of non-financial firm listed at Indonesia Stock Exchange period 2009. Earnings management is measured by working capital accruals. Auditor reputation is measured by dummy variable Big Four Auditors and Non-Big Four Auditors. Hypothesis test is done by applying Independen Sample T-Test. The result shows that mean of accruals of firms audited by Big Four Auditor is higher than mean of accruals of firms audited by Non-Big Four Auditor. But, the accruals not statistically significant. Keywords: earnings management, auditor reputation, Big Four versus Non-Big Four Auditors.